From elementary particles to the limits of the infinite cosmos - Talios, Vaggelis (Nova Science Publishers, Inc., 2020)
"The book describes our up-to-date knowledge of the Universe and suggests a new theory, the "Theory of the Chain Reaction", which explains the creation and the functioning of the material part of our Universe and the whole Cosmos. The first five chapters described herein cover the evolution of human knowledge about the Universe, the Universe as it is known today, the elementary particles and the fundamental forces, the theory of the big bang and the other existing cosmological theories about the creation. After the above, the author presents the "Theory of the Chain Reaction", a revolutionary theory that explains in an original and innovative way the creation and the evolution of our Cosmos. Next the reader will find the answers, according to the "Theory of the Chain Reaction", to some questions that still remain unanswered today about the creation such as where have the huge amounts of energy that exist in the universe been found? Does antimatter exist and, if so, where is it? Etc. The last chapter is a brief summary of the theory of the unification of the fundamental forces and physical theories. This chapter, in any case, is an introduction to the subject of the unifications and was written for readers who want to know more about this issue"-- Provided by publisher.
Keywords: Quarks.; Matter -- Constitution.; Particles (Nuclear physics); Cosmology.; Elementary Particles; Matière -- Structure.; Particules (Physique nucléaire); Cosmologie.; particle physics.; cosmology.; Cosmology; Matter -- Constitution; Quarks